2019
DOI: 10.1155/2019/2710509
|View full text |Cite
|
Sign up to set email alerts
|

Yangyin Yiqi Mixture Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Rats through Inhibiting TGF-β1/Smad Pathway and Epithelial to Mesenchymal Transition

Abstract: Objective The aim of the current study was to investigate the protective effect of Yangyin Yiqi Mixture (YYYQ) on Bleomycin-induced pulmonary fibrosis in rats based on TGF-β1/Smad signal pathway and epithelial to mesenchymal transition (EMT). Methods 120 Wistar rats were randomly divided into six groups: control group, BLM group, BLM + Pred group, BLM+YYYQ-L group, BLM+YYYQ-M group, and BLM+YYYQ-H group. Rats were given an intratracheal instillation of 3 mg/kg BLM to establish the pulmonary fibrosis model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The development of fibrosis can be seen biochemically and histologically. The results of histopathological analysis showed that the main pathological manifestations of lung tissues were marked by collagen deposition, congested blood capillaries and alveolitis, which developed into pulmonary fibrosis 19,23 . The increased mitochondrial ROS, the disrupted membrane potential, the congested blood capillaries and alveolitis, and collagen deposition caused by BLM were also mitigated upon concurrent treatment with NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of fibrosis can be seen biochemically and histologically. The results of histopathological analysis showed that the main pathological manifestations of lung tissues were marked by collagen deposition, congested blood capillaries and alveolitis, which developed into pulmonary fibrosis 19,23 . The increased mitochondrial ROS, the disrupted membrane potential, the congested blood capillaries and alveolitis, and collagen deposition caused by BLM were also mitigated upon concurrent treatment with NAC.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β1, a profibrotic factor, plays an important role in resulting multiple organ fibrosis through increasing the production of glucose and proteoglycans, promoting the transport of amino acids and the deposition of extracellular matrix 23 . During the process of pulmonary fibrosis, the increase of TGF‐β1 induces the up regulation of CTGF, which promotes the proliferation and differentiation of fibroblasts and collagen production 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, collapsed alveoli may be also due to vascular congestion and depletion of the pulmonary surfactant [ 40 , 41 ]. However, the presence of dilated alveoli could be result of epithelial, endothelial and basement membrane damage [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, YYYQ induced the expression of Smad7 and E-cadherin in the BLM group and the prednisolone-treated BLM group. Therefore, it was supposed to be related to suppressing the EMT and TGF-β1/Smad signaling pathways [ 229 ]. Total alkaloids from Alstonia Scholaris (L.) R. Br.…”
Section: Natural Products Against Pulmonary Fibrosis With Specific Me...mentioning
confidence: 99%
“…This also enhanced the activity of SOD in the serum and lung tissues. Moreover, the alkaloid treatment resulted in decreased TGF-β and MMP-1 expressions [ 229 ]. Ophiocordyceps lanpingensis polysaccharides (OLP) alleviated collagen deposition and oxidative stress and decreased macrophage accumulation.…”
Section: Natural Products Against Pulmonary Fibrosis With Specific Me...mentioning
confidence: 99%